Self-Control with Social Media Addiction in Students of SMA Negeri 3 Kota Kupang - Dorothea Lidyaprima Bheo; M. Dinah Charlota Lerik; R. Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2020)
Social media addiction can be seen as a form of internet addiction, in which individuals show an urge to use social media excessively. A person's inability to control himself to connect to the internet is the cause of internet addiction. The purpose of this study was to determine the relationship between self-control and social media addiction in students of SMA Negeri 3 Kota Kupang. The sampling technique used convenience sampling with a total sample size of 117 subjects. The analysis in this study used non-parametric correlation analysis Spearman Rank. The results of hypothesis testing using the Spearman correlation technique obtained a correlation coefficient of -0.387 with a significance level of 0.000 (P> 0.05). This means that there is a significant negative relationship between self-control and social media addiction in SMA Negeri 3 Kota Kupang. This study concluded that the higher the social media addiction, the lower the self-control in SMA Negeri 3 Kota Kupang and vice versa.